An Extremely Rare Case of Prostate and Bladder Wall Involvement of Chronic Lymphocytic Leukemia - Mathew Thomas; Ali Wazir; Shridevi Karikehalli; Michael Sandhu; Aarati Poudel (SAGE Publishing, 2023)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults and is characterized by monoclonal proliferation of B-cell lymphocytes which are morphologically mature, but immunologically dysfunctional. The primary sites of disease involvement include peripheral blood, lymph nodes, spleen, and bone marrow. CLL can also present locally and aggressively at extranodal sites. We describe the case of a 74-year-old gentleman with multiple medical comorbidities who was Foley catheter-dependent at baseline for bladder outlet obstruction. He was detected to have Rai stage I CLL following an inguinal lymph node biopsy and was on regular outpatient surveillance. Later, he underwent a prostate biopsy for evaluation of hematuria, results of which were consistent with CLL involvement in the prostate and urinary bladder. The patient was started on single-agent ibrutinib, and demonstrated an excellent clinical response to bladder outlet obstruction. His long-term Foley catheter was discontinued within 5 days of ibrutinib therapy. Unfortunately, 1 year later, he had disease progression, and therapy was changed to a single-agent rituximab, to which he is responding well. Our case is unique as it brings up the first reported case of prostate and bladder wall CLL.